"Senti-pensar" la transfronteridad. - Cangi, Adrián (Hermenéutica, 2023)
Colonizing European modernity only retained for its conquests the negative sense of "frontier" as an "abstract limit" (nec plus ultra), while Amerindian cultures experienced it in a positive way (being in the in-between place of mixtures and transits). The oldest sense of "limit" is where the "uncertainty of an identity" reigns that confronts the mixture of the own with the strange, of the confinement of the site and the openness beyond. It is the space in which it is possible to live, in the double sense of inhabitare and colere, which means "converting a space into land for cultivation and worship", to the point of "constituting it as a language colony". Limes is simultaneous "space" and "enclosure" for the configuration of a colony. For this reason, the senses of limes (space, fence) are linked to that of limen (threshold, lintel). Gloria Anzaldúa writes "On the Border / you are the battlefield...", and forces us to think about "cross-border". Transborder is considered as the crossing of limits between national territories, and therefore the notion is thought of as a multinational or transnational problem. Is it possible to imagine a community devoid of fair hospitality and legal protection that acts in reality with respect to the migration that runs through it and lacerates it? How can the law immunize the hostile violence that runs through the community against the other migrant without allowing itself to be swallowed up?